2021
DOI: 10.1186/s13223-021-00571-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene–gene and gene-environment interactions on cord blood total IgE in Chinese Han children

Abstract: Background IL13, IL4, IL4RA, FCER1B and ADRB2 are susceptible genes of asthma and atopy. Our previous study has found gene–gene interactions on asthma between these genes in Chinese Han children. Whether the interactions begin in fetal stage, and whether these genes interact with prenatal environment to enhance cord blood IgE (CBIgE) levels and then cause subsequent allergic diseases have yet to be determined. This study aimed to determine whether there are gene–gene and gene-environment intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As a result, these studies have suggested interaction effects of known asthma genes with environmental tobacco smoke exposure during childhood ( IL1RN , NFE2L2 ), 31,32 and a novel locus for asthma susceptibility ( NAT1 ) 33 (Table 2). Furthermore, the association of in utero exposure with genetic variants in asthma has been evaluated 34 . Additionally, Sugier et al 35 carried out one of the few GWIS published to date evaluating the effects of tobacco smoke.…”
Section: Interactions Between Genes and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, these studies have suggested interaction effects of known asthma genes with environmental tobacco smoke exposure during childhood ( IL1RN , NFE2L2 ), 31,32 and a novel locus for asthma susceptibility ( NAT1 ) 33 (Table 2). Furthermore, the association of in utero exposure with genetic variants in asthma has been evaluated 34 . Additionally, Sugier et al 35 carried out one of the few GWIS published to date evaluating the effects of tobacco smoke.…”
Section: Interactions Between Genes and The Environmentmentioning
confidence: 99%
“…Furthermore, the association of in utero exposure with genetic variants in asthma has been evaluated. 34 Additionally, Sugier et al 35 carried out one of the few GWIS published to date evaluating the effects of tobacco smoke. Specifically, the significant interaction of four novel loci with exposure to cigarette smoke was revealed to potentially influence the time-to-asthma onset in children from European populations 35 (Table 3).…”
Section: Inter Ac Ti Ons B E T Ween G Ene S and The Environmentmentioning
confidence: 99%
“…The SNP that was most analyzed in the number of studies (22 studies, 75.86%) associating IL-4 with asthma in different populations was rs2243250, with the T allele, a mutant highlighted by susceptibility in 15 studies (51.72%): Finnish and Russian 33,39 ; Chinese 37,50 ; Portuguese 38 ; Indian 40 ; Taiwanese 41 ; German 42 ; North-american 44,54 ; Filipinos 45 ; Italian 53 ; Pakistani 58 ; British 59 ; and Dutch population 60 . In an Iraqi population, the C, wild allele conferred greater susceptibility to asthma 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The rs2243250 SNP is an upstream variant (5') of the promoter region of the gene found at residue position 589. With regard to the change that occurred in the gene in relation to the function of IL-4, there is an effect of transcriptional addition, with an increase in the binding affinity of transcription factors, leading to overexpression of IL-4 mRNA, generating a phenotype susceptible to asthma and reducing the levels of pro-inflammatory cytokines, increasing the production of IgE and the induction of overexpression of IgE receptors in airway mast cells, resulting in increased recruitment of eosinophils 50,65,66 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study has shown that the four-locus model consisting of IL-13 gene R110Q (IL-13 R110Q), IL-4 gene-590C>T, recombinant adrenergic receptor beta 2 R16G (ADRB2 R16G), and Fc epsilon receptor Iβ E237G (FCER1B E237G) is the best predictor of respiratory disease susceptibility genes in children (8). Among them, ADRB2 and FCER1B have been confirmed to have a close relationship with changes in respiratory function, and are considered as new clinical markers for future risk assessment of neonatal congenital diseases (9,10). Hence, we speculate that ADRB2 and FCER1B gene polymorphisms may have the same potential early evaluation function for congenital respiratory diseases in PTIs, but no studies have been conducted to support our view.…”
Section: Introductionmentioning
confidence: 99%